Large and in charge: cortisol levels vary with sex, diet, and body mass in an Antarctic predator, the leopard seal - Sperou, Emily S.; Crocker, Daniel E.; Borras-Chavez, Renato; Costa, Daniel P.; Goebel, Michael E.; Kanatous, Shane B.; Krause, Douglas J.; Trumble, Stephen J.; Kienle, Sarah S. (Frontiers in Marine Science, 2023)
Evaluating physiological responses in the context of a species’ life history, demographics, and ecology is essential to understanding the health of individuals and populations. Here, we measured the main mammalian glucocorticoid, cortisol, in an elusive Antarctic apex predator, the leopard seal (Hydrurga leptonyx). We also examined intraspecific variation in cortisol based on life history (sex), morphometrics (body mass, body condition), and ecological traits (δ15N, δ13C). To do this, blood samples, life history traits, and morphometric data were collected from 19 individual leopard seals off the Western Antarctic Peninsula. We found that adult leopard seals have remarkably high cortisol concentrations (100.35 ± 16.72 μg/dL), showing the highest circulating cortisol concentration ever reported for a pinniped: 147 μg/dL in an adult male. Leopard seal cortisol concentrations varied with sex, body mass, and diet. Large adult females had significantly lower cortisol (94.49 ± 10.12 μg/dL) than adult males (120.85 ± 6.20 μg/dL). Similarly, leopard seals with higher isotope values (i.e., adult females, δ15N: 11.35 ± 0.69‰) had lower cortisol concentrations than seals with lower isotope values (i.e., adult males, δ15N: 10.14 ± 1.65‰). Furthermore, we compared cortisol concentrations across 26 closely related Arctoid taxa (i.e., mustelids, bears, and pinnipeds) with comparable data. Leopard seals had the highest mean cortisol concentrations that were 1.25 to 50 times higher than other Arctoids. More broadly, Antarctic ice seals (Lobodontini: leopard seal, Ross seal, Weddell seal, crabeater seal) had higher cortisol concentrations compared to other pinnipeds and Arctoid species. Therefore, high cortisol is a characteristic of all lobodontines and may be a specialized adaptation within this Antarctic-dwelling clade. Together, our results highlight exceptionally high cortisol concentrations in leopard seals (and across lobodontines) and reveal high variability in cortisol concentrations among individuals from a single location. This information provides the context for understanding how leopard seal physiology changes with life history, ecology, and morphology and sets the foundation for assessing their physiology in the context of a rapidly changing Antarctic environment.